Genetic algorithm for task mapping in embedded systems on a hierarchical architecture based on wireless network on chip WiNoC (2017)
Network on Chip (NoC) systems were originally developed to provide high performance, using the availability of several processing units, connected to a wired network inside the integrated circuit. Wireless NoC (WiNoC or WNoC) are a natural evolution of NoC systems, which integrate a hierarchical communication inside the chip for the sake of improving scalability. Task mapping in WNoC systems represents a challenging process, which often involves several optimization objectives, such as power, performance, throughput, resources usage, and network metrics. This paper describes a genetic algorithm based approach for finding optimal tasks-mapping solutions in design time, for embedded systems working over a WiNoC. The optimization objectives were: Speedup, Energy Consumption, and Bandwidth. The target network used for simulation may be viewed as a two-level hierarchical WiNoC. The first level corresponds to a set of subnets which are linked by wires and mesh-type. The second level corresponds to a star-topology of wireless links, which connect the first level subnets. Proposed algorithm exhibits a good performance in relation to the optimization objectives, concerning the target heterogeneous WiNoC.